ANALISIS CAPAIAN PERKEMBANGAN KOGNITIF PADA ANAK USIA DINI DI TKIT NURUL FALAH KOTA BATAM - Qory Ismawaty (STAI Miftahul Ulum Tanjungpinang, 2023)
Cognitive abilities play a very important role in life because almost all aspects of life require cognitive abilities. Cognitive abilities are needed by children to be able to learn various things. Children's thinking ability is influenced by their cognitive development. This study aims to analyze the achievement of children's cognitive development at TKIT Nurul Falah Batam City which involved 15 children and 2 teachers. This type of research is descriptive qualitative. Data collection methods used are observation, interviews and documentation. Data analysis was carried out in three steps, namely data collection, data reduction and data presentation. The results showed that learning activities were carried out by applying group learning models and using loose part-based learning media, namely used bottles and caps, sand, twigs, flowers, and others. The achievements of children's cognitive development have developed very well including learning abilities and problem solving, logical thinking abilities and symbolic thinking abilities.